2015
DOI: 10.1080/15548627.2015.1058474
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei survival in lung epithelial cells benefits from miRNA-mediated suppression of ATG10

Abstract: (2015) Burkholderiapseudomallei survival in lung epithelial cells benefits from miRNA-mediated suppression of ATG10, Autophagy, 11:8, 1293-1307, DOI: 10.1080/15548627.2015 Keywords: ATG10, autophagy, Burkholderia pseudomallei, DNA methylation, MIR4458, MIR4667-5p, MIR4668-5pAbbreviations: 3-MA, 3-methyladenine; 3 0 UTR, 3 0 -untranslated region; 5-Aza-CdR, 5-aza-2 0 -deoxycytidine; ACTB, actin, b; ATG4C, autophagy-related 4C, cysteine peptidase; ATG5, autophagy-related 5; ATG10, autophagy-related 10; ATG12, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Another pathogen, Burkholderia pseudomallei promotes its replication in the cytosol of murine macrophages by evading LC3 targeting through an undefined process involving the type III secretion system ATPase BpscN[38]. In addition, infection of macrophages and epithelial cells with B. pseudomallei or Burkholderia cenocepacia leads to downregulation of certain autophagy genes, resulting in decreased levels of autophagy[39,40]. Group B streptococcus (GBS) induces autophagy during infection of EC, but still resides primarily in single membrane-bound compartments, suggesting that GBS evades targeting to autophagosomes[41].…”
Section: Xenophagy Beyond M Tuberculosis As Revealed By Cell Culturementioning
confidence: 99%
“…Another pathogen, Burkholderia pseudomallei promotes its replication in the cytosol of murine macrophages by evading LC3 targeting through an undefined process involving the type III secretion system ATPase BpscN[38]. In addition, infection of macrophages and epithelial cells with B. pseudomallei or Burkholderia cenocepacia leads to downregulation of certain autophagy genes, resulting in decreased levels of autophagy[39,40]. Group B streptococcus (GBS) induces autophagy during infection of EC, but still resides primarily in single membrane-bound compartments, suggesting that GBS evades targeting to autophagosomes[41].…”
Section: Xenophagy Beyond M Tuberculosis As Revealed By Cell Culturementioning
confidence: 99%
“…Autophagy-related 10 gene ( ATG10 ), which encodes an E2-like enzyme ( 25 ), interacts with ATG7 to receive an ubiquitin-like protein ATG12, recognizes both ATG12 and ATG5 directly and catalyzes their conjugation reaction ( 26 28 ). ATG10 has been shown to play an important role in the invasion and proliferation of cancer cells ( 8 , 29 ), and bacterial infections ( 30 ). At present, the research of the function of ATG10 alone is lacking, and few studies have examined the interdependency between the structure and function of ATG10.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial invasion of A549 cells followed our previously described strategy [10], with minor modifications. A549 cells were diluted to 1.5 × 10 5 /mL, and 1 mL cell suspension was plated in each well of a 12-well plate containing glass coverslips (NEXT, China).…”
Section: Infection Confocal Microscopy and Mgcs Formationmentioning
confidence: 99%
“…It has been reported that B. pseudomallei can escape into the cytoplasm by inducing rearrangement of host actin cytoskeleton and with the help of its type III secretion system (T3SS) effector proteins, such as BopE and BopA [7][8][9]. Our team previous research found that B. pseudomallei could evade autophagy by 3 novel miRNAs of MIR4458, MIR4667-5p, and MIR4668-5p targeted regulation of ATG10 in A549 cells [10]. Macrophages could up-regulate Rab32 GTPase through reducing miR-30b/30c to accelerate B. pseudomallei-containing phagosomes maturation [11].…”
mentioning
confidence: 91%